Dynamics of training and competition demands in top-class male rink hockey: a case study of a rink hockey European Championship - Ferraz, A.; Duarte-Mendes, P.; Ribeiro, J. N.; Yousefian, F.; Valente-dos-Santos, J.; Travassos, B. (International Journal of Performance Analysis in Sport, 2024)
This study aimed to investigate the training load through external and internal load dynamics across the preparation and competition of a top-level national team during a Rink Hockey European Championship. A non-experimental descriptive method was developed. A two-way mixed design ANOVA and a Spearman correlation test were used to compare and understand the relationship between players` external and internal load across microcycles during training sessions and competitive matches. Results revealed significantly higher values between training match day -3 to training match day -1 for player load (p = 0.05), distance covered, and high-speed skating (p = 0.001). Competition weeks exposed significantly higher values in comparison with training weeks. Interestingly, during competition, high impacts (p = 0.001, r = 0.64) and decelerations (p = 0.001, r = 0.43) had a greater influence on players` session RPE than in training weeks. Different external and internal load dynamics were observed in the competition and training weeks, with high impacts and decelerations appearing to create a physiological impact on players, but the same does not occur in the training sessions. Results highlight the need to understand the competitive dynamics of each sport and the use of the most appropriate metrics to monitor the preparation process.